THE INFLUENCE OF TOP-DOWN STRATEGY (TDS) ON STUDENTS’ READING COMPREHENSION - Dwi Darsa Prasetyo; Ummi Khaerati Syam; Saiful Saiful; Ismail Sangkala (Universitas Muhammadiyah Makassar, 2018)
This research aimed to find out the influence of Top-Down Strategy (TDS) on students reading comprehension that focus on level of literal and interpretative of comprehension. The researcher applied pre-experimental method with one group pre-test and post-test. The sample of this research was class XI MIA 2 of SMA Negeri 10 GOWA which consisted of 30 students. The sample was taken by using purposive sampling method. The result of the research were the mean score of pretest in Literal (main Idea) score of pretest was 58.6 and post-test was 86.56. In sequence of detail the score of pretest was 56.4 and post-test was 92.6 with t-test value Literal is greater than t-table (13.26 2.45). Mean score of intrepretative in pretest was 63.63 and post-test was 82 with the t-test value is greater that t-table (8.34 2.45). The result of calculating t-test of the indicators in the students’-test (Literal and Interpretative) was greater than t-table 21.60 2.45. it means that there was significance different between before and after giving the treatment. Based on explanation above we concluded that using Top-Down Strategy is influence and improve students reading comprehension especially in literal and interpretative levels.